THE EFFECT OF OPEN UNEMPLOYMENT RATE, POPULATION GROWTH, AND HDI ON POVERTY RATE IN CENTRAL JAVA PROVINCE 2024 - Malik, Yusuf Maulana; Furqon, Imahda Khoiri (Islamic Economic and Business Journal, 2025)
One of the socioeconomic problems that every region is responsible for is poverty. Poverty is a social problem that has existed for a long time and is difficult to eradicate until now. The majority of developing countries, including Indonesia, experience poverty. Poverty is influenced by low human resources, low natural resources, and low quality of education. This study uses secondary data, namely data provided by BPS (Central Bureau of Statistics). Data collection techniques are carried out through documentation, namely direct data collection from related agencies and some literature related to the problem to be studied and then recorded and processed. The results showed that partially the variable Open Unemployment Rate (X1) and Population Growth X2 did not have a significant effect on Poverty (Y) in Central Java in 2024. However, the HDI variable (X3) has a significant effect on Poverty (Y).